Correlation between Vocabulary Mastery, Reading Habits, and English Reading Comprehension Achievements in Students of State Elementary School Gunungsari 01 Pati - Ida Hendriyani; Andreas Heri Kurniawan (Universitas Palan, 2026)
This study uses a one group pretest posttest design model. posttest on the correlation between vocabulary mastery, reading habits, while pretest with conventional learning, then both groups were measured with the same measuring instrument. To test whether the two data (variables) are the same or different, a t-test was conducted. The t-test obtained a t count of 2.082 with α = 0.05 and t table = 1.725. The testing criteria in the one-tailed test are Ho is rejected and H1 is accepted if t count > t table. The hypothesis can be accepted because t count > t table, namely 2.082 > 1.725. The results of student learning completeness show a significant percentage, namely the pretest gets 10 (50%) students who have not completed and 10 (50%) students who have completed after being carried out on the correlation between vocabulary mastery, reading habits get completeness posttest learning results 18 (88.89%) students who have completed and 2 (11.11%) students who have not completed. It was concluded that through the correlation between vocabulary mastery, students' reading habits can achieve learning completeness because it is one indicator of the effectiveness of this research. The conclusion is that the correlation between vocabulary mastery, reading habits is effective in achieving English reading comprehension for fifth grade students of Gunungsari 01 Pati State Elementary School. Based on the results of this study, the suggestion obtained is that the correlation between vocabulary mastery and reading habits be used as an alternative for teachers to teach English in class.